PENDAMPINGAN SDM GURU MADRASAH DINIYYAH MELALUI PELATIHAN MANAJEMEN PESERTA DIDIK PONDOK PESANTREN DARUL FALAH BULUREJO PURWOHARJO BANYUWANGI - Aimah, Siti; Harun Al Rosid, Moh.; Nasih, Muhammad (Proceedings of Annual Conference on Community Engagement, 2023)
Teachers at madrasah diiayah need to be provided with assistance in empoering and increasing their competence, especially in implementing student management. This importing to do considing that teachers are the main actorsin education and this still not widely done in madrsah diniyah, especially in pesantren. Madrasah at Pesantren Darul Falah Bulurejo Purwoharjo Banyuwangi it was chosen as an assited location because it has potential that is whorty of development, namey the human resources of eachers and he motivation of student. The purpose of this assistance is so that Madrasah Diniyah Pesantren Darul Falah Bulurejo teachers receive assistance in student management to strenghtenhman resources, nderstand and implement them well and there is good synergi between IAIDA Blokagung and the madrasah. Using the Particiption tion Research (PAR) method, the result of this research show that theachers at he madrasah diniyah afer receiving assistance through student mangement training were able toimprove their competence in the early education learning process better.